Linguistic Features and Generic Structures in Discussion Writing: A Case Study at Politeknik Negeri Media Kreatif - Liza Amalia Putri (Jurnal Ilmiah Publipreneur, 2020)
What kind of linguistic features and generic structures do the students of Politeknik Negeri Media Kreatif use in their discussion writing? This study aims at analyzing the linguistic features and generic structures found in the students’ writing. The SFL Theory of Genre covering linguistic features and generic structures by Gerot and Wigmel is used to analyze the data. The study uses the descriptive qualitative research method and analyzes the writing of the students who have learned how to write discussion essay. The finding is that the dominant linguistic feature of all the texts is the generic human and non-human participants. All students follow the rules of writing: the generic structure, the arguments for, the arguments against and the conclusion or recommendation. The students have put all linguistic features in their discussion writing.